Les parlers urbains vus par les nomades - Souheila HEDID (Lengas)
The data used in this study is drawn from a field survey conducted in the city of Constantine from a nomadic tribe "Ouled Nail". The objective was to understand the socio-linguistic representations that these speakers develop about the different urban dialects they encounter during their travels. The study is thus based on an analysis of an authentic epilinguistic corpus mainly composed of interviews. The methodological framework of this research is based on a triangulation of the tools of investigation, an approach that has allowed us to validate the data collected and to confirm the results.